Enabling business networking within suburban development - Suvi Konsti-Laakso; Timo Pihkala; Saara Linna (European Regional Science Association (ERSA), 2010)
Small and middle sized companies (SME) are important for local economies. Networking of SME is often considered to be a vital activity as well in production operations but also in innovation activities (Vesalainen 2006, Bessant and Tidd 2007.) From the perspective of small businesses the value networks (Vanhaverberke & Cloodt 2006) provide an interesting opportunity. Instead of mere value chain co-operation, the value networks open up new approaches to horizontal co-operation and opportunity to use the small businesses' own core competencies in a wider context. While the access to traditional value chain networks has been dominantly difficult for the smallest businesses, in value networks the access is largely dependent on the entrepreneur's personal contacts and social relationships. The purpose of this paper is to analyze the formation process of a SME value network focusing on the development of a small suburb. Through this analysis we seek to illustrate how regional Living Lab activities can promote SME networking. The theory section provides an insight about value network, user involvement in innovation and network evolution. The case example is from Lahti Living Lab, where a group of companies from living environment (products or services such as living area services, parks, street maintenance, planning, communication and outdoor products) participate in suburb development.
Keywords: 330; SME networking; user driven development; living lab; urban revitalization